PENINGKATAN PRODUKTIFITAS DAN DAYA SAING PRODUK TORTILA BERBASIS JAGUNG (ZEA MAYS) - Widya Dwi Rukmi Putri; Nur Ida Panca Nugrahini; Elok Waziiroh (JISIP : Jurnal Ilmu Sosial dan Ilmu Politik, 2016)
Abstract: "KUBE" MadepManteb engaged in the processing of corn to to provide added value in the main commodity of village. This group is composed of 20 industrial household food which cooperate together in improving the quality of products and marketing. Product of KUBE "MadepManteb is tortillas with a variety of flavors. Some problems KUBE "MadepManteb is the lack of efficiency in production due to inadequate equipment, packaging products that are less interesting as well as the need to improve the quality of the product. Through IbM solution provided include 1) Increasing the efficiency and capacity of stirring the dough tortillas, 2) Increased efficiency and capacity cutting sheet tortillas, 3) Improved draining oil products tortila to prevent rancidity during distribution, 4) Increasing the efficiency of mixing dry seasoning with tortillas, 5) Repair of packaging products to increase competitiveness, and 6) Assistance improvement of product quality. Activity Increased efficiency and production capacity is done with the technology transfer of industrial equipment, namely automatic dough mixer 5 kg capacity, semi-automatic cutting sheet tortillas, spinner oil drainer, mixer dried herbs and stove industry. Manufacture of packaging design and procurement of packaging materials for the improvement of the packaging as an effort to increase the competitiveness of tortillas. Improved quality of products is done with extension How Good Food Production and mentoring for troubleshooting problems during the use of production equipment. Keywords:tortilla, productivity, competing capacity, technology Abstrak.Kelompok Usaha Bersama “KUBE” Madep Manteb bergerak di bidang pengolahan jagung untukmemberikannilaitambahpadakomoditiutamadesatersebut.Kelompok usaha ini terdiri dari 20 industri rumah tangga pangan yang saling berkerja sama dalam peningkatan mutu produk dan pemasaran. Produk unggulan dari KUBE” Madep Manteb adalah tortila dengan berbagai varian rasa. Beberapapermasalahan yang KUBE” Madep Mantebadalahkurangnyaefisiensiproduksiakibatperalatan yang kurangmemadai, pengemasanproduk yang kurangmenariksertaperlunyapeningkatanmutuproduk.MelaluikegiatanIbMinisolusi yang diberikanmeliputi 1) Peningkatanefisiensidankapasitaspengadukan adonan tortila, 2) Peningkatanefisiensidankapasitaspemotong lembaran tortila, 3) Perbaikan penirisan minyak produk tortila untuk mencegah ketengikan selama distribusi, 4) Peningkatan efesiensi pencampuran bumbu kering dengan tortila, 5) Perbaikankemasan produk untuk peningkatan daya saing, dan 6) Pendampinganpeningkatanmutuproduk. KegiatanPeningkatanefisiensidankapasitasproduksidilakukandenganalihteknologiperalatanindustriyaitupengaduk adonan otomatis kapasitas 5 Kg, pemotong lembaran tortila semi otomatis, peniris minyak spinner, pengaduk bumbu keringdankomporindustri. Pembuatandesainkemasansertapengadaanbahanpengemasdilakukanuntukperbaikankemasansebagai upaya peningkatan daya saing produk tortila.Perbaikanmutuprodukdilakukandenganpenyuluhan Cara ProduksiPangan yang Baiksertapendampinganuntuktroubleshootingpermasalahanselamapenggunaanperalatanproduksi. Kata kunci :tortila, produktivitas, daya saing, alih teknologi